Effects of Phytogenic Additives and Organic Acids, alone or in combination, on the Performance, Intestinal Quality and Immune Responses of Broiler Chickens - Fascina,VB (2017)
ABSTRACT The present study was conducted to evaluate the effects of phytogenic additives (PA) and organic acids (OA), alone or in combination, on the performance, intestinal histomorphometry and lipid oxidation, and immune responses of broiler chickens. In this experiment, 820 one-day-old chicks were distributed according to a completely randomized design in a 2 × 2 + 1 factorial arrangement, with four replicates of 41 broilers each. The dietary treatments consisted of a control diet with no PA or OA (CD); CD with OA and no PA (CD+OA-PA); CD with PA and no OA (CD+PA-CD); CDwith both PA and OA (CD+PA+CD); and CD + avilamycin + monesin sodium. Broiler performance was not affected by the alternative feed additives, except from 1 to 21 days, when broilers fed the CD or CD+PA+OA diets showed higher body weight gain than those fed the CD with only OA. The broilers fed the diet containing avilamycin and monensin presented better performance. The supplementation of PA and OA increased bursalcortical area on21 and 42 days post-hatch. On 21 days post-hatch, broilers fed the AGP diet presented higher ileal villus height than those fed the control diet. The pH values of the jejunum content were reduced on the OA-fed chickens. Higher villus height and crypt depth were found in the alternative additive-fed chickens on 7 days post-hatch. On 42 days post-hatch, the percentage of the bursal cortex increased in PA-fed broilers; however, there was no increase in antibody production. The PA-fed chickens presented lower thiobarbituric acid reactive substances (TBARS) values in the small intestine. The dietary supplementation of phytogenic additives, individually or in combination associated with organic acids, does not affect broiler live performance or intestinal histomorphometry; however, it enhances immune responses and intestinal quality.